Pelatihan Bagi Aparat Desa dalam Pengelolaan Arsip Digital Menuju Desa Tertib Administrasi di Desa Kelungkung Kabupaten Sumbawa - Edi Irawan; Fitria Permata Cita; Rozzy Aprirachman (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Organizing digital village governance is very important. This is due to the widespread need for accurate and fast availability of information on village development. The objective to be achieved in this service activity is to carry out training for Village Officials Kelungkung in the context of utilizing digital archives for structuring the administration of village government. The method used is knowledge transfer through training and assistance in using Google Drive as a medium for archive management and presentation of information for village government officials. The result of this activity is an increase in knowledge and skills as evidenced by changes in behavior on a scale of 76-100, namely the high category. This is also evidenced by an increase in the understanding of concepts and practices of participants in digital document management in Kelungkung Village on average increased by 25%. The results of this activity are expected to provide solutions to archival problems in Kelungkung Village, Sumbawa Regency, towards an orderly administrative village.